PENGENALAN PENGOLAHAN SUSU KAMBING DI KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR [Introduction of Goat Milk Processing in Sub-district of Sukadana, District of East Lampung of the Lampung Province] - Wylis, Ratna; Santri, Novilia; Asnawi, Robet (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
Milk is easily damaged when handling is poor, so it has a relatively short shelf life. To handle the excess milk production, the most appropriate step is to preserve milk to extend the shelf life through processing, and at the community level the consumption of processed milk is higher than the consumption of fresh milk. This research was conducted in Muara Jaya Village, Sukadana District, East Lampung Regency, from June to August 2016 with Mentari’s women farmer group as cooperator. The types of processed goat milk introduced are goat’s milk with spice flavoured, goat’s milk ice cream with strawberry tasted, goat’s milk ice cream with kweni tasted, and goat’s milk caramel candy. The products of goat’s milk are tested on consumer preference and its counted breakeven price for each kind of product, so it is known how much the price of kind of processed goat’s milk if it want to commercialized. Observation parameters included, proximate analysis for fresh goat’s milk, consumer acceptance rate and break even price of each kind of product. Observation of consumer acceptance level is done by using hedonic scale (scale 1-5) from 20 panelists and breakeven price is calculated by comparing total production cost with yield produced. The collected data were analyzed statistically and if there was difference of the mean value was continued with DMRT test at 5% level. The results showed that the development of goat’s milk preparation is very pospective because goat’s milk has high protein content and low fat content so good for health; Processed goat’s milk produced introduced by the consumer, with a mean score> 3; The result of break even analysis shows that goat milk processing has prospect to be developed, because the price of its break even point is still reached by consumer that is: Rp.45.500, -/ liter goat’s milk spice flavoured; Rp. 61.267/liter goat’s milk ice cream strawberry tasted, Rp.55.933, -/ liter goat’s milk ice cream kweni tasted, and Rp. 1.479 /goat’s milk caramel candy.